The Effect of Price, Service Quality at Customer Satisfaction Mediated by the Purchase Decision at PT Maybank Indonesia Finance during the Covid-19 Pandemic - Perdana Putera; Melitina Tecoalu; Soegeng Wahyoedi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study discusses the effect of price, service quality on customer satisfaction mediated by purchase decisionss at PT Maybank Indonesia Finance during the covid-19 pandemic. This type of research is descriptive with probability random sampling method that uses 100 online questionnaires from 121 consumer respondents of PT MayBank Indonesia Finance. The data analysis technique in this study is the Structural Equation Model (SEM) using SmartPLS 3.0. Tests were carried out with the outer model, inner model and hypothesis testing of p-value and t-statistics. The results showed that price had a significant effect on customer satisfaction and purchase decisionss, service quality had a significant effect on purchase decisionss and had no effect on customer satisfaction, purchase decisions had a significant effect on customer satisfaction, then price had an effect on customer satisfaction mediated by purchase decisionss and service quality. influence on customer satisfaction which is mediated by purchase decisionss.